m2-49=0

Add 49 to both sides of the equation.

m2=49

Take the square root of both sides of the equation to eliminate the exponent on the left side.

m=±49

Simplify the right side of the equation.

Rewrite 49 as 72.

m=±72

Pull terms out from under the radical, assuming positive real numbers.

m=±7

m=±7

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

m=7

Next, use the negative value of the ± to find the second solution.

m=-7

The complete solution is the result of both the positive and negative portions of the solution.

m=7,-7

m=7,-7

m=7,-7

Solve using the Square Root Property m^2-49=0